Toxicity Of Jatropha curcas and Cymbopogon nardus Extracts Against Pests Callosobruchus chinensis On Mung Beans - ardiansyah, sigit; Wahyudi, Anung; Nuryanti, Ni Siluh Putu (Al-Hayat: Journal of Biology and Applied Biology, 2022)
Callosobruchus chinensis L. is an important pest on mung beans. Alternative control of C. chinensis using botanical insecticides from extracts of Jatropha curcas and Cymbopogon nardus. The purpose of the research was to compare the toxicity of extracts and determine their compatibility. Toxicity testing methods use to contact, fumigation, and seed dressing methods. The research data was tested by probit analysis. The results showed that the toxicity of the contact method extract was more toxic than fumigation and seed dressing. The highest LC50 and LC95 values for the C. nardus extract applied with the contact method were observed at 72 HAT at 0.17% and 0.40% more toxic than the J. curcas extract at 0.21% and 2.14%. The best mixed extract of J. curcas and C. nardus was at a ratio of 2:1 with strong synergistic interaction (LC50) and weak synergy (LC95).